2017
DOI: 10.1155/2017/7876942
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutative Relativistic Spacetimes and Worldlines from 2 + 1 Quantum (Anti-)de Sitter Groups

Abstract: The -deformation of the (2 + 1)D anti-de Sitter, Poincaré, and de Sitter groups is presented through a unified approach in which the curvature of the spacetime (or the cosmological constant) is considered as an explicit parameter. The Drinfel' d-double and the Poisson-Lie structure underlying the -deformation are explicitly given, and the three quantum kinematical groups are obtained as quantizations of such Poisson-Lie algebras. As a consequence, the noncommutative (2 + 1)D spacetimes that generalize the -Min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 106 publications
(284 reference statements)
2
31
0
Order By: Relevance
“…Notice that this coproduct is written in a "bicrossproducttype" basis that generalizes the one corresponding to the (2 þ 1) κ-AdS ω algebra [44,45]. As it can be easily checked, the κ-Poincaré coproduct (2) is obtained from the above expressions in the limit ω → 0.…”
Section: The κ-(A)ds Algebra and Its Dual Poisson-lie Groupmentioning
confidence: 98%
See 2 more Smart Citations
“…Notice that this coproduct is written in a "bicrossproducttype" basis that generalizes the one corresponding to the (2 þ 1) κ-AdS ω algebra [44,45]. As it can be easily checked, the κ-Poincaré coproduct (2) is obtained from the above expressions in the limit ω → 0.…”
Section: The κ-(A)ds Algebra and Its Dual Poisson-lie Groupmentioning
confidence: 98%
“…(iii) The Minkowski spacetime M 3þ1 ≡ ISOð3; 1Þ= SOð3; 1Þ arises when ω ¼ Λ ¼ 0. Explicit ambient space coordinates for these three maximally symmetric Lorentzian spacetimes can be obtained by making use of a suitable realization of the Lie groups obtained by exponentiation of a faithful representation of the AdS ω Lie algebra [see [43][44][45] for details in the (2 þ 1)-dimensional case].…”
Section: The κ-(A)ds Algebra and Its Dual Poisson-lie Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is well-known that most of the structures that can be defined on classical homogeneous spaces of geodesics can be inherited from their associated motion groups. For instance, in [43] all symplectic, complex and metric structures were described, and we recall that in [39] all homogeneous spaces of worldlines corresponding to kinematical groups were studied in detail, including the pseudo-Riemannian metrics defined on them, and in [44] the (2+1) Lorentzian spaces of worldlines were considered. In particular, for the Poincaré case it was found that an invariant foliation exists in the space of worldlines and that the resulting homogeneous space is of negative curvature (see [39] for details).…”
Section: Introductionmentioning
confidence: 99%
“…At this point it could seem surprising that the noncommutative (A)dS spacetimes (64) and (66) do not depend on the cosmological constant and, therefore, coincide with the corresponding noncommutative Minkowski spacetimes. Indeed, this is true only at first order, and higher order contributions depending on are expected to appear when the full quantum coproduct z is constructed and the all-orders noncommutative spacetime is obtained by applying the full Hopf algebra duality or, alternatively, by quantizing the allorders Poisson-Lie group whose linearization corresponds to the extended noncommutative spacetimes here presented (see [50][51][52] for explicit examples, including the noncommutative κ-(A)dS spacetime in (2 + 1) dimensions, which turns out to be a nonlinear deformation of the κ-Minkowski spacetime).…”
Section: C2 Whenmentioning
confidence: 99%